2023
DOI: 10.3390/nu15051215
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Dietary Deprivation: Migrant Households in Nairobi, Kenya

Abstract: The current study focuses on food consumption and dietary diversity among internal migrant households in Kenya using data from a city-wide household survey of Nairobi conducted in 2018. The paper examined whether migrant households are more likely to experience inferior diets, low dietary diversity, and increased dietary deprivation than their local counterparts. Second, it assesses whether some migrant households experience greater dietary deprivation than others. Third, it analyses whether rural-urban links … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…In the current work, the low income of the migrant population was associated with low dietary diversity. The same finding was reported in a study from Kenya in 2018 25 . Indeed, the global economic and financial crisis, poor buying power, and rising food costs would encourage individuals to avoid purchasing particular food products 26 .…”
Section: Discussionsupporting
confidence: 89%
“…In the current work, the low income of the migrant population was associated with low dietary diversity. The same finding was reported in a study from Kenya in 2018 25 . Indeed, the global economic and financial crisis, poor buying power, and rising food costs would encourage individuals to avoid purchasing particular food products 26 .…”
Section: Discussionsupporting
confidence: 89%
“…Some households also received food from friends and relatives in urban areas. However, in another study, Onyango et al [ 24 ] also focused on the length of stay in the city, rural-urban links, and food transfers, which did not focus on the dietary diversity of households in Nairobi. Nonetheless, the results reported by Onyango et al [ 22 ] are further supported by Merchant et al [ 23 ], who found that urban households reported lower food security outcomes than rural households because of decreased access to the food production environment resulting from COVID-19 restrictions on movement and lockdowns.…”
Section: Conceptual Approachmentioning
confidence: 99%
“…Ericksen [ 25 ] also identifies other factors, such as access to government and non-government social support services, as food production and consumption determinants. Besides the rural-urban food continuum, employment, education, household income, and food prices also determine food security outcomes [ 23 , 24 ]. These studies highlight the importance of socioeconomic variables in determining food security.…”
Section: Conceptual Approachmentioning
confidence: 99%
See 2 more Smart Citations